Impact of Microbial Load on the Bioremediation of Crude Oil Polluted Soil - Nwokedi, Fadila (My University, 2023)
The effect of microbial load and nutrient (NPK 15:15:15) on crude oil polluted soil was investigated in this study. 10% crude oil polluted soil for the samples were impacted with Aspergillus niger of concentrations 1×106 cfu/g, 2×106 cfu/g, 5×106 cfu/g, 1×107 cfu/g, 2×107 cfu/g respectively and NPK 15:15:15 were introduced to five samples which served as test samples, and the other as control sample. Parameters such as pH, Residual Hydrocarbon Content (RHC), Total Microbial Count (TMC) were monitored over a period of seven (7) weeks. The results obtained show an increase in pH for the samples. The Total Hydrocarbon Content (THC) decreased for all the samples. The control sample dropped from 183-27mg/kg (85% drop), sample impacted with 1×106 cfu/g dropped from 179-10mg/kg (94% drop), sample impacted with 2×106 cfu/g dropped from 181-9mg/kg (95% drop), sample impacted with 5×106 cfu/g dropped from 181-8mg/kg (96% drop), sample impacted with 1×107 cfu/g dropped from 180-6mg/kg (97% drop) and the sample impacted with 2×107 cfu/g dropped from 184-4mg/kg (98% drop). From the results, bioremediation strategy was found to be very effective.
Keywords: Aspergillus Niger; Bioremediation; Microbial load; Nutrient (NPK 15:15:15); pH; Residual Hydrocarbon Content (RHC); Total Hydrocarbon Content (THC); Total Microbial Count (TMC)